DETEKSI PARASIT DARAH PADA KUCING LIAR (STRAY CATS) DENGAN METODE PEWARNAAN MDT DI PASAR TRADISIONAL SURABAYA - Hermawan, Intan Permatasari; Sari, Dian Ayu Kartika; Rahman, Mohammad Noor (JURNAL KAJIAN VETERINER, 2021)
The aim of this study was to detect blood parasites of stray cats with an MDT staining test. Total samples were 40 blood taken from 4 markets in Surabaya, every market took 10 samples of stray cats. Three (3) cc Blood took from vena cephalica antebrachial anterior or vena saphena. Then blood samples were stained using MDT and checked under microscope 1000 magnification. The result showed 7 positive (17,5%) Anaplasma sp from 40 samples. This study needs advanced diagnosis using PCR, antibody detection (IFA test), ELISA, and western immunoblot assay although blood staining was detected by the agent.